ANALISIS HARGA SAHAM DALAM KONDISI KRISIS - Asy'ari, Asy'ari (Fakultas Ekonomi, Program Studi Akuntansi, 2018)
The paradigm of stocks and crises is very inherent in the world of investment, especially if the value of the rupiah exchange rate against the dollar shows declining fluctuations. High inflation results in changes in prices of commodities or goods that are traded internationally. This will also lead to changes in the shares of a company related to international trade transactions. This study aims to determine the type of stock in the object under study, in a state of crisis. This study uses a qualitative approach with sample shares of companies engaged in food. The results show that stocks engaged in food and beverages do not show a declining trend in stock prices, especially as stock prices are always stagnant.